(untitled) (Medico Legal Update, 2020)
Background/Objectives: When acquiring medical images using X-ray, optimal medical imaging quality must be achieved with minimal exposure of the x-ray generator. Method/Statistical Analysis: The experiment was conducted based on the exposure conditions that are mainly used in the clinic. The exposure conditions of Hand, Skull, and Chest examinations were determined as the test subjects, and X-Rays were exposed to each partial phantom. The original data was obtained by exposing X-Rays three times for each phantom, and the values of the pixels were analyzed using the Image J program. Findings: As the transmitted dose increased, the pixel value increased in proportion to the average intensity. As the X-ray exposure conditions were reduced, the maximum, minimum, and average values of the entire pixel were lowered. In step 1, which is the basic exposure condition of Hand, the average value of all pixels was reduced from 818.311 in step 5, which was the lowest exposure condition. Similar reductions were observed in the skull and chest exposure. When the pixel value is viewed as the transmitted dose value, it is confirmed that the pixel value of the image reflects the transmitted dose value. Signal-to-noise ratios varied with exposure conditions. Improvements/Applications: These results alone made it difficult to find the optimal transmission dose for making images. Additional measurements of the doses exposed at each step will yield better results. Later we will continue to study through more diverse and accurate experiments.